2005
DOI: 10.1063/1.1863442
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of NiSi∕Si Schottky barrier heights by sulfur segregation during Ni silicidation

Abstract: The Schottky barrier height ͑SBH͒ of NiSi on Si͑100͒ was tuned in a controlled manner by the segregation of sulfur ͑S͒ to the silicide/silicon interface. S was implanted into silicon prior to silicidation. During subsequent Ni silicidation, the segregation of S at the NiSi/ Si interface leads to the change of the SBH. The SBH of NiSi decreased gradually on n-Si͑100͒ from 0.65 eV to 0.07 eV and increased correspondingly on p-Si͑100͒. © 2005 American Institute of Physics. ͓DOI: 10.1063/1.1863442͔ Self-aligned si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
62
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(68 citation statements)
references
References 13 publications
6
62
0
Order By: Relevance
“…by inserting a thin insulator layer [3] or by creating a highly doped region located at the silicide/Si interface with a dopant segregation technique [5]- [6]. To our knowledge, no such reports were available for hole SBH modulation.…”
Section: Introductionmentioning
confidence: 99%
“…by inserting a thin insulator layer [3] or by creating a highly doped region located at the silicide/Si interface with a dopant segregation technique [5]- [6]. To our knowledge, no such reports were available for hole SBH modulation.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, a NiSi contact to n-type Si(100) still suffers from a reasonably high Schottky barrier (∼ 0.65 eV) deteriorating the contact resistance [2]. The midrange band gap of NiSi in fully silicided (FUSI) gates on the other hand requires a modulation of the work function [3].…”
Section: Introductionmentioning
confidence: 99%
“…To make the SBFETs comparable to state-of-the-art short-channel MOSFETs in terms of drivability, the intrinsic SBH should be lowered to ∼100 meV [3]. Recently, it has been shown that the effective electron SBH could be lowered by inserting a thin insulator [3] or a highly doped layer (defined with a dopant segregation technique [5], [6]) at the silicide/Si junction. To our knowledge, no such method has already been reported for hole SBH.…”
Section: Introductionmentioning
confidence: 99%